Legal Aspects of Micro Business Development Institutions in State Purpose of Welfare - Lukmanul Hakim; Etty Mulyati; Djuhaendah Hasan; Tarsisius Murwadji (Universitas Lampung, 2020)
Micro-business is one of the activities that is currently almost 90% the share of business in Indonesia, considering the micro business is an informal business, and not many micro-businesses have been touched by the financing sector so that micro-businesses are not affected in the economic crisis. In addition, micro-businesses are complicated to develop their businesses due to the lack of requirements to get funding and guidance that is still not effective, resulting in the lack of information for businesses to take advantage of existing market share. Moreover, micro-businesses must also be able to adapt to continue and grow amidst the current difficult conditions. The problems in this study are 1. Growth of Micro Businesses and the Concept of Development and Funding amid Technology-Based Business Competition 2. Legal Aspects of Micro-Business Development in the Welfare State's Goals. Results of this Research As the goal of the welfare state is one of them to improve the social welfare of the community. Micro-businesses participate in the purpose of the welfare state because remembering micro business as one of the fundamental pillars of driving the economy in Indonesia. It is necessary to have an active role of government and society to participate in building micro-businesses to be more developed so that the increase of the economy both in the region and nationally. So that the government must be able to facilitate businesses so that micro businesses can develop as the objectives of the welfare state.